Development of interactive learning media assisted by Articulate Storyline 3 based on Android to improve the ability to understand mathematical concepts at SMPN 3 Stabat - Fadila Khairunisa; Dian Armanto (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the quality (validity, practicality and effectiveness) of the results of the development of android-based Articulate Storyline 3-assisted interactive learning media to improve the ability of students to understand mathematical concepts that have been developed. This research is research and development or RD (Research and Development) that uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects in this study are 30 students in grades VIII-2 SMPN 3 Stabat. The data collection techniques used in this study are interviews, observations, questionnaires and tests of mathematical concept comprehension ability. Based on the results of the validation of interactive learning media assisted by Articulate Storyline 3 based on android to improve the ability to understand mathematical concepts that have been developed by media experts and subject matter experts, an average percentage of 93% and 96.3% was obtained which was categorized as